2015
DOI: 10.1155/2015/609053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium Supplementation on Redox Status of the Aortic Wall in Young Spontaneously Hypertensive Rats

Abstract: Selenium (Se) is an exogenous antioxidant that performs its function via the expression of selenoproteins. The aim of this study was to explore the effect of varying Se intake on the redox status of the aortic wall in young spontaneously hypertensive rats (SHR). Sixteen male Wistar Kyoto (WKY) rats and nineteen male SHR, 16-week-old, were tested after being given diets with different Se content for eight weeks. They were divided into 4 groups: control groups of WKY NSe and SHR NSe on an adequate Se diet and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Decreased levels of GPx activities were observed in progressive hypothyroidism in the postnatal period [43]. Reduced activities of GPx, one of the most important antioxidant defense systems in the body, either reported increased or decreased intracellularly in different tissues antioxidant enzymes [44,45]. Increased GPx activity experimental colitis was reported in the parotid glands of mice; decreased enzyme activity was found in submandibular glands [46].…”
Section: Glutathione Peroxidasementioning
confidence: 99%
“…Decreased levels of GPx activities were observed in progressive hypothyroidism in the postnatal period [43]. Reduced activities of GPx, one of the most important antioxidant defense systems in the body, either reported increased or decreased intracellularly in different tissues antioxidant enzymes [44,45]. Increased GPx activity experimental colitis was reported in the parotid glands of mice; decreased enzyme activity was found in submandibular glands [46].…”
Section: Glutathione Peroxidasementioning
confidence: 99%
“…Results that were confirmed within in vitro studies using HUVECs, which demonstrated increased eNOS expression and activity with accompanying NO production upon Se supplementation [68]. Conflicting data does exist, however, with studies utilising spontaneously hypertensive rats (SHR) demonstrating that SeMet supplementation decreased eNOS expression within the aortic wall [69]. A limitation of the current study is that eNOS activity and the levels of NO were not assessed, which may have particular relevance to the 12 w HFD cohort, given that SeMet supplementation decreased iNOs expression under these conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Se oral supplementation in the form of a pill is widespread, and is available as an over-the-counter drug to the general population. It is well accepted that oxidative stress is one of the main contributors to endothelial dysfunction, and since Se is recognized for its proposed atheroprotective function and its antioxidant and anti-inflammatory properties, it is surprising that there is still a paucity of inconsistent data on the vascular effects of dietary Se modulation in both experimental animal and human studies [ 17 , 18 ]. For example, a sub-study of the SUpplementation en VItamines et Minéraux AntioXydants (SU.VI.MAX) study has shown no marked beneficial effects of long-term daily low-dose supplementation of antioxidant vitamins (vitamin C and E, beta carotene) and minerals (Se) on carotid structure and arterial stiffness in healthy middle-aged volunteers [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that an increased activity of Se-dependent GPx might prevent ROS-induced protein and DNA damage, while TRs are named accordingly by their ability to reduce oxidized thioredoxin (Trx) [ 16 ]. Furthermore, a growing body of evidence indicates that endothelial selenoproteins are involved in the regulation of: (1) the vascular tone by maintaining the superoxide anion/NO balance; (2) cell adhesion by controlling cell adhesion molecule expression; (3) apoptosis via inhibition/activation of apoptosis signal-regulating kinase-1; and (4) eicosanoid production by controlling the activity of the cyclooxygenase 1 and 2 (COX-1, 2) and lipoxygenases [ 17 , 18 ]. Accordingly, it became evident that Se and Se-contained enzymes may be directly involved in the regulation of vascular inflammatory processes and atherogenesis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation